Efektivitas Penegakan Hukum Pemilu (Peran Bawaslu Kota Sungai Penuh dalam Pemilihan Kepala Daerah Tahun 2020) - Ansorullah Ansorullah; Iswandi Iswandi; Firmansyah Putra (University of Udayana, 2023)
The holding of elections is inseparable from electoral institutions, namely the General Election Commission and the Election Supervisory Body in accordance with the Election Law and the Pilkada Law. Seeing the legal facts that occur in Indonesia and especially the Election of Regional Heads in the City of Sungai Penuh, a problem that always arises and occurs and this becomes an interesting discussion for organizers and the public is the effectiveness of law enforcement, especially election crimes. This study aims to examine the implementation of Bawaslu's authority in terms of handling election crimes and the effectiveness of law enforcement regarding criminal acts in the 2020 Regional Head election in Sungai Penuh City. The research method used is empirical juridical, using primary data and secondary data which is then analyzed using qualitative data analysis. The results of this study conclude that there are several problems in election law enforcement, namely: The regulation is still weak regarding mechanisms and procedures in law enforcement on election crimes. Differences in viewpoints regarding roles, authorities and responsibilities between The General Election Supervisory Agency, the Police and the Attorney. Community participation is still not optimal in the framework of election supervision. Facilities and infrastructure as well as recalculating the cost of organizing in handling cases of election violations. Penyelenggaraan pemilu tidak terlepas dari lembaga kepemiluan yaitu oleh Komisi Pemilihan Umum dan Badan Pengawas Pemilu sesuai dengan UU Pemilu dan UU Pilkada. Melihat fakta hukum yang terjadi di Indonesia dan khususnya Pemilihan Kepala Daerah di Kota Sungai Penuh, permasalahan yang selalu muncul dan terjadi serta hal ini menjadi diskusi menarik bagi penyelenggara dan masyarakat adalah efektivitas penegakan hukum khususnya tindak pidana pemilu. Penelitian ini bertujuan untuk mengkaji pelakasanaan kewenangan Bawaslu dalam hal penanganan tindak pidana pemilu dan efektivitas penegakan hukum atas tindak pidana pemilu Kepala Daerah di Kota Sungai Penuh Tahun 2020. Metode penelitian yang digunakan adalah yuridis empiris, dengan menggunakan data primer dan data sekunder yang kemudian dianalisis dengan menggunakan analisis data kualitatif. Hasil penelitian ini menyimpulkan bahwa terdapat beberapa masalah dalam penegakan hukum pemilu, yaitu: Masih lemahnya pengaturan terkait mekanisme dan prosedur dalam penegakan hukum tindak pidana pemilu. Perbedaan sudut pandang tentang peran, wewenang dan tanggung jawab antara Bawaslu, Kepolisian dan Kejaksaan. Partisipasi masyarakat yang masih belum optimal dalam rangka pengawasan pemilu, serta menghitung kembali biaya pengorganisasian dalam penganan kasus pelanggaran pemilu.